Melanoidin removal in multi-oxidant supplemented microwave system: Optimization of operating conditions using response surface methodology and cost estimation. (February 2020) - Tripathy, Binay Kumar; Johnson, Inigo; Kumar, Mathava
Graphical abstract: Highlights: Melanoidin (250 mg/L) was completely removed (10 min) in MW-PS process (PS-2500 mg/L). MW-PS/H2 O2 process (PS: H2 O2 -2500:3000 mg/L) achieved 60% melanoidin removal (10, 000 mg/L) after 10 min. CCD was able to predict response with less error in cubic model compared to quadratic model. Cost estimation shows reduction in specific cost with increased melanoidin concentration. Abstract: Melanoidin removal in a microwave (MW) coupled with persulfate (PS) and/or hydrogen peroxide (H2 O2 ) system was investigated. As a precursor, batch-mode MW-PS experiment was conducted at 250 mg/L of melanoidin concentration. The removal was observed to be 100% in 20 min of MW irradiation at PS dose of 2500 mg/L and it was found that the rate constant increased with PS dosage. On the other hand, the MW-H2 O2 process has shown 31% removal at 6000 mg/L H2 O2 dosage in 20 min. A central composite design (CCD) was used to identify the interaction between melanoidin concentration (500–10000 mg/L), pH (2–12), H2 O2 (0–6000 mg/L) and PS (0–5000 mg/L) dosages on melanoidin removal in MW system. The basic condition (pH > 7) has shown higher melanoidin removal in the presence of H2 O2 /PS; however, proportionate decrease in removal was observed with increase in melanoidin concentration. The addition of H2 O2 and PS has amplified the removal of colour induced by melanoidin, which was modeled by quadratic (R 2 -0.87) and cubic (R 2 -0.98) regression models. A set of validation experiments were carried out under model predicted optimum conditions. The experimental observations were in good correlation with the cubic model predicted values. Alcohol scavenging experiment shows that both sulfate and hydroxyl radical are responsible for melanoidin removal. The generation of hydroxyl radicals was estimated. A simple first-order kinetic equation-based model was developed to calculate the cost per kg of melanoidin removal in MW-PS/H2 O2 system. Overall, MW-PS/H2 O2 system seems to be a better alternative for high-rate melanoidin removal.